Article RETRACTED due to manipulation by the authors Traditional games for physical fitness: an experimental study on elementary school students - Irvan Septianto; Sumaryanti Sumaryanti; Ahmad Nasrulloh; Sulistiyono Sulistiyono; Hartman Nugraha; Masnur Ali; Aria Malik Ramadhani; Julian Dewantara; Nida Haniyyah; Fauzi Fauzi; Didi Suryadi; Roy Ardian; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Maintaining optimal physical fitness is crucial for students to combat fatigue during activities, allowing them to concentrate on their studies during the learning process at school. Consequently, physical fitness is a fundamental aspect of health that warrants careful consideration. The objective of this study is to enhance students' abilities and promote good physical fitness through the utilization of traditional games. The research employed a pre-experimental design with a one-group pretest-posttest approach. Modified traditional games, including sodor carts, fish nets, and balloon racing, were applied as the treatment.The results of the treatment demonstrated a significance value of 0.000, indicating a notable increase in students' physical fitness after engaging in learning activities through traditional games. This improvement is attributed to the traditional games, which effectively engage children in learning, fostering active participation and contributing to the enhancement of physical fitness. Consequently, the conceptualization of physical learning within the framework of traditional games proves to be applicable and effective.